Legal Aspects of Memorandum of Understanding from the Legal Perspective of Contract Law in the Civil Code - J.E. Melky Purba (PT. Sinergi Legal Publisher, 2025)
Memorandum of understanding(MoU) or memorandum of understanding is an instrument frequently used in business relations and institutional cooperation in Indonesia, both by private and public legal entities. However, until now the Civil Code has not explicitly regulated the term MoU, thus giving rise to debate regarding its status and binding force from the perspective of contract law. On the one hand, MoUs are often positioned merely as moral bonds or gentlemen's agreements that do not give rise to legal consequences of contract. On the other hand, the view is growing that MoUs that have fulfilled the essential elements of an agreement can actually be treated as binding agreements as agreements under the Civil Code. This study aims to analyze the legal aspects of the MoU from the perspective of the law of obligations in the Civil Code, specifically in relation to Article 1313, Article 1320, and Article 1338 of the Civil Code, and examine whether the MoU can be qualified as an agreement or only a preliminary agreement. The method used is normative juridical with a statutory and conceptual approach through a literature study of classical and contemporary literature on the law of obligations and the MoU. The results of the study indicate that the position of the MoU is largely determined by the content and intentions of the parties. If the MoU only contains the main points of global cooperation, without any concrete obligations, the MoU tends to be understood as a morally binding pre-contract. However, if the MoU contains essential clauses of the agreement and meets the requirements for a valid agreement, then the MoU can be qualified as an agreement that gives rise to an obligation and is therefore subject to the regime of default and civil liability. Thus, the certainty of the position of the MoU requires careful formulation of the content, as well as the affirmation of the parties' objectives from the beginning of its preparation.